Age Discrimination, Apprenticeship Training and Hiring: Evidence from a Scenario Experiment - Axana Dalle; Toon Wybo; Stijn Baert; Dieter Verhaest (Institute of Labor Economics (IZA), 2024)
In many countries, age discrimination appears to be driven by negative perceptions that recruiters stereotypically hold about older candidates' technological skills, trainability, and flexibility. Based on human capital, signalling, and screening theories, we hypothesise that training programmes might both compensate for and mitigate these ageist stereotypes and thereby improve these candidates' hiring chances. We test this pathway out of age discrimination by designing a scenario experiment in which professional recruiters assess the recruitability and human capital perceptions of fictitious candidates varying in age and (willingsness for) participation in apprenticeship training at older ages. Our results demonstrate that candidates indicating their (willingness for) participation in such training to obtain relevant work experience are more likely to be recruited than candidates without such experience, regardless of their age. Although apprenticeship training can compensate for age discrimination, it cannot mitigate this as the premium it yields is not higher for older workers.
Keywords: J14; J24; J71; 330; hiring discrimination; older workers; labour market programmes; apprenticeships; signalling; scenario experiment